Analisis Escherichia coli dan Zat Kimia pada Minuman Es Jagung - Khairani , Tetty Noverita; Fitri , Khairani; Tarigan, Rida Evalina; Khairani, Cut; Natasya, Alfa (Journal of Pharmaceutical and Sciences, 2025)
The addition of inappropriate food additives (BTM) such as artificial sweeteners, and synthetic dyes which are added intentionally by food vendors is one of the problems that cause food not suitable for consumption because it can cause health problems. The purpose of this study was to analyze the dyes, sweeteners and E.coli in corn ice drinks sold in Pakam. The study design uses qualitative laboratory analysis. The population in this study is the corn ice traders in the city of Lubuk Pakam, amounting to 5 traders. The sample consisted of 5 traders who were in the Regent's Office, Galang Street, Segangular Field, Labu Beach and Ahmad Dahlan Street. The work procedure is by checking the coloring agent, sweetener and Escerichia coli examination. The results of laboratory tests revealed that the coloring agents in samples A and E contained Tartrazine and in samples B, C and D contained Tartrazine and Sunset Yellow, sweeteners were found in samples C and E and in samples A, B and D were not found to contain artificial sweeteners and 5 samples (100%) showed a total value of escerichia coli <3 APM / ml per ml sample. The conclusion in this study is that corn ice drinks sold in the city of Lubuk Pakam use coloring agents and sweetening agents that are permitted based on the Republic of Indonesia Ministerial Regulation No. 033 of 2012 and containing Escerichia coli of <3 APM / ml are still within the allowed limits in accordance with the Indonesian National Standard (SNI) and the Head of Indonesian National Drug and Food Control Agency Regulation No. HK.00.06.1.52.4011.